Climate Change-An Emblematic Driver of Vector-Borne Diseases: Holistic View As A Way Forward - Yusuf Amuda Tajudeen; Iyiola Olatunji Oladunjoye (University of New South Wales, 2021)
Vector-Borne Diseases (VBDs), including malaria, arboviruses, Lyme diseases, leishmaniasis and many others, have become an important public health threat across the globe due to rapid climate change. This is due to the alteration of the geographical distribution of vectors, which in turn amplify the spread of diseases. In this article, we highlight climate change as an emblematic driver of vector-borne diseases, as well as explicate its positive correlation with the increased prevalence of vector-borne diseases, citing relevant studies as evidence. Consequently, we recommend that researchers from different disciplines, including ecologists, metagenomics and modeling experts, climate scientists, microbiologists, wildlife experts, entomologists, public health scientists, social scientists, religious and community leaders, legal practitioners, and policy-makers, should work together under the One Health approach supported by government and political leaders to mitigate the global threat of vector-borne diseases.